The impact of modern global art movements on Graphic Design (Al-Academy, 2016)
The significant shift in the Fine Arts, who led the avant-garde movements and creative which appeared in the modern, specifically in the mid-nineteenth century and early twentieth century era path, embodied in a clear show of new aesthetic value rejects traditional methods put in shape and color qualities She described the movements subjectivity or no formal, was intended to determine the direct function of expression and speech language in the visual arts away from the representation and simulation of reality was accompanied by the appearance of those fine movements directed towards a global approach to design carries features and clear in its organizations formalism of the most important move away from the symmetry and the adoption of rather than the system and attention to the job which was considered one of the basic principles of beauty and order to reach the roots of the global method in graphic design stages undergone by the design history, combined with Fine art avant-garde movements, In the most important historical era, appeared at the researcher problem and found worthy Find summed it up by asking follows what is the impact of modern art movements on graphic design in the modern age in determining the formal building and expressive attributes and achieve career goals aesthetic from here came the goal of research statement formalism and organizational variables for graphic designer and performance expressive and comparing methods affected artistic movements of the modern era. The research based on analytical descriptive approach to group samples came out of her with Group of conclusion : findings and conclusions, namely: contributed to modern art in creating standards performance today, a new process aesthetic design, which was limited to the aesthetic drawing and techniques to express them into a collage techniques and photo montage about metaphor expressive use of materials has not been touched before., To achieve the formal organization of the elements with the background, whether from during the mathematical logic and engineering or coincidence industry led to a shift in the design process and the emergence of new space relationship directly influenced in a clear transformation of the design